Wheat blast disease: Bangladesh and global perspectives of blast resistance: Wheat blast disease resistance (Journal of the Bangladesh Agricultural University, 2019)
Fearsome wheat blast disease expanded its radius from Latin America to Bangladesh in 2016 with higher degrees of destruction efficiency. In 1985, Brazil was the first hotspot and consecutively Paraguay, Argentina, Bolivia were affected by the wheat blast fungus. Blast fungus Magnaporthe oryzae is under pyriculariaceae family with three-celled, pyriform, hyaline conidia. Not only wheat and rice are affected by the blast pathogen but also around 50 grass species can be affected and act as host, but the fungus pathotype is specific and distinct for each plant species. Morpho-biometrical analysis revealed similarity between the Magnaporthe oryzae pathotype Tritici (MoT) strain of Bangladeshi and Brazil. Through extensive molecular genetics and genomics study unfolded five resistant genes, among those Rmg2, Rmg3, and Rmg7 lost viability but Rmg8 and RmgGR119 still have resistance. In addition, 2NS translocation from Aegilops ventricosa in wheat reports resistance against MoT. CIMMYT based Milan variety is regarded as a resistant variety and plant breeders are trying to develop new resistant varieties. But the main problem regarding blast pathogen is breakdown of resistance and evolving virulent races consecutively which is fueled by global warming. A wide range of molecular markers can potentially be used for blast resistance study. Utilization of medium to high-throughput markers like SSR, InDel and SNP gave pace in blast resistance study. Along with that, allele mining has potentiality for finding out source of resistance. In addition, gene pyramiding will play a vital role in introgression of multiple resistant genes into a superior wheat linage. In future, high-throughput marker technology along with cutting-edge gene editing technology will play a pivotal role. Furthermore, the collaborative research in Bangladesh indicates that international scientific community has taken wheat blast as a serious issue.J. Bangladesh Agril. Univ. 17(2): 122–132, June 2019